An Overview and State of The Art in Reconfigurable Antennas with Their Applications - El Aoud Salah Eddine; Abbaoui Hind; Attioui Sanae; El Assri Nasima; Ibnyaich Saida; Zeroual Abdelouhab (ITM Web of Conferences)
Reconfigurable antennas represent a critical innovation in modern wireless communication, offering dynamic control over antenna parameters such as frequency, radiation pattern, and polarization. This adaptability is essential in addressing the increasing demands of next-generation communication systems, including 5G/6G networks, cognitive radios, and the Internet of Things (IoT). By integrating technologies like PIN diodes, MEMS, and tunable materials, reconfigurable antennas can adjust to varying environmental and operational conditions, providing enhanced performance in terms of bandwidth, efficiency, and interference mitigation. Recent developments in the field focus on miniaturization, multi-band operation, and integration with advanced technologies like artificial intelligence (AI) for intelligent reconfiguration. Smart materials, such as metamaterials and liquid crystals, offer new ways to achieve greater flexibility in antenna design. Applications of reconfigurable antennas are expanding across various sectors, from aerospace and defense to healthcare and wearable devices. Despite significant progress, challenges remain in optimizing cost, power consumption, and reliability.